TINJAUAN SYARIAT TERHADAP ZAKAT PROFESI DARI HASIL YOUTUBER DENGAN METODE QIYAS ZAKAT EMAS - Afthon Yazid; Fauzia Ulirrahmi; Ilman Nur Alam (Universitas Islam Malang, 2022)
YouTuber is one of the jobs that millennials are increasingly interested in. Although the income generated is not still like an employee, but there are some YouTubers who are able to gain income up to billion as well. A lot of income, becomes a study for the rules of zakat profession, where there are rights that must be excluded from the income obtained. Zakat on profession is part of zakat mal and becomes a contemporary of fiqh, so a lot of controversion in there. The controversion is part of the prudence of the scholars in establishing the sharia law of zakat on profession, one of which is used qiyas. This research aims to find out the sharia law of zakat on profession for youtuber by using qiyas of zakat on gold. This research used a qualitative descriptive approach that focused on the study of literature. The results of the analysis showed that by qiyas of zakat on gold, Muslim YouTubers are obliged to issue zakat on proffesion if the net income obtained if it reaches the nisab of gold, which is 85 grams of gold with a level of 2.5% and reaches haul.